Surface oxygen vacancies and carbon dopant co-decorated magnetic ZnFe2O4 as photo-Fenton catalyst towards efficient degradation of tetracycline hydrochloride. (September 2022) - Fang, Yuanyuan; Liang, Qianwei; Li, Ying; Luo, Hanjin
Abstract: Carbon doped strategy has been recognized as an efficient strategy to enhance photo-Fenton degradation performance. However, the preparation of high efficiency C-doped photocatalyst has been a significant challenge. Herein, we synthesized magnetic carbon-doped ZnFe2 O4 via a facile solvothermal-calcination route. The photo-Fenton activity of C-doped ZnFe2 O4 under visible light (λ > 420 nm) was evaluated by degradation of tetracycline hydrochloride. C-doped sample, CZF-2 (0.5 g L −1 ) presented excellent removal performance for TC-HCl (20 mg L −1 ) in presence of H2 O2 (10 mM) and could remove 90.8% of TC-HCl within 50 min. The C-doping modulates crystal defects and generates surface oxygen vacancies simultaneously, thus building a new C-doping level near valence band and a defect level under the conduction band. Meanwhile, surface oxygen vacancies bring photo-generated electrons and electrons generated from itself to surface to accelerate photo-Fenton reaction, and the holes are rapidly transferred to the surface to participate in the degradation of pollutants. Graphical abstract: Image 1 Highlights: The developed CZF-2 could remove 90.8% of TC-HCl (20 mg L −1 ) within 50 min. The synergetic effect of H2 O2 and visible light was proved. Abundant oxygen vacancies exist on the surface of c-doped zinc ferrite. The modification mechanism of carbon doping is demonstrated. ·OH, h + and O2 − are the main reactive species in CZF-2/H2 O2 /vis system.